Intralesional bleomycin injection in management of low flow vascular malformations in children. Issue 2 (April 2014) - Mohan, Anita T.; Adams, Saleigh; Adams, Kevin; Hudson, Donald A
Abstract: Low flow vascular malformations are challenging to manage, particularly with their propensity to grow, and can lead to severe disfigurement and dysfunction. Traditional surgical excision is fraught with tedious dissection and complications, particularly in the head and neck region. Trends toward less invasive techniques, such as intralesional sclerotherapy, are proving to be successful independent treatments or adjuncts in management in low flow vascular malformations. This study was a retrospective case note review, over an 8-year period, reporting the outcomes of 32 children (mean = 5.8 years, range = 5 months–11.5 years) with radiologically confirmed low flow vascular malformations, treated with serial intralesional bleomycin injection (IBI) therapy. Patient demographics, lesion characteristics, imaging findings, treatment course, radiological and clinical response to treatment were recorded. An overall 91% ( n = 29) response rate was achieved, with 28% obtaining complete resolution for low flow vascular malformations. Lesions were sub-categorized into venous malformation, including mixed venous-capillary ( n = 27) or lymphatic malformation (LM) ( n = 5). Twenty-seven of 32 children experienced no complications. Local complications included superficial skin infection ( n = 2), skin necrosis ( n = 1), hyperpigmentation, and minor contour deformity. There was no recurrence and no systemic side-effects to bleomycin. Mean follow-up was 38 months (range = 6–95 months). In conclusion, serial intralesional bleomycin injections can be effective and also safe in a paediatric population for the successful management of symptomatic or disfiguring low flow vascular malformations.